2010
DOI: 10.1016/j.jmb.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Oligomeric States of the Yeast Rvb1/Rvb2 Complex Induced by Histidine Tags

Abstract: SUMMARYRvb1 and Rvb2 are essential AAA+ helicases, which are important components of critical complexes such as chromatin remodeling and telomerase complexes. The oligomeric state of the Rvbs has been controversial. Independent studies from several groups have described the yeast and human Rvb1/Rvb2 complex both as a single and a double hexameric ring complex. We found that histidine tagged constructs of yeast Rvb proteins employed in some of these studies induced the assembly of double hexameric ring Rvb1/Rvb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
37
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 26 publications
11
37
2
2
Order By: Relevance
“…In that study, however, ExbD carried a StrepII affinity tag at its carboxy terminus and ExbB carried a His 6 tag. Epitope tags have resulted in artifactual protein interactions or prevented native interactions, described in multiple protein systems where histidine tags were used (8,19,47). Within the TonB system, ExbD oligomerization states are affected by epitope tagging.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, however, ExbD carried a StrepII affinity tag at its carboxy terminus and ExbB carried a His 6 tag. Epitope tags have resulted in artifactual protein interactions or prevented native interactions, described in multiple protein systems where histidine tags were used (8,19,47). Within the TonB system, ExbD oligomerization states are affected by epitope tagging.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of an N-terminal histidine tag in yeast Rvb1 or Rvb2 induces the formation of double hexameric ring structures [19,22]. Recently, the structure of the yeast SWR1 [23] and INO80 [24] chromatin-remodeling complexes have been obtained by cryo-EM.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…+ proteins typically assemble into single hexameric rings (34), but examples exist where such proteins form double-hexameric ring structures (35)(36)(37). The SEC analysis suggested that Pch2 assembles into a single hexameric ring.…”
Section: Aaamentioning
confidence: 99%
“…Importantly, no additional higher molecular bands that could represent a dodecameric or higher-order complex of Pch2 were observed. As a control, we loaded a mixture of RuvBlike (Rvb)1 and Rvb2 AAA + proteins under conditions where they oligomerize both as single (∼300 kDa) and double (∼600 kDa) hexameric ring structures (36). These oligomers have theoretical molecular masses similar to the expected mass of Pch2 hexamers and dodecamers.…”
Section: Aaamentioning
confidence: 99%